Optimizing the Performance of the Kamsel Satlantas Unit through the Police Goes to School Program to Increase Student Traffic Safety Awareness in the Jurisdiction of Sragen Police Station - Hidayat, Rahmat (Advances in Police Science Research Journal, 2024)
Accidents that appeared at the Sragen Police Station have increased in recent years and have claimed many lives and high material losses. The high number of accident cases involving students must be addressed because students are the next generation of the nation nor assets that must be protected so the inculcation of traffic safety understanding from an early age is very important. Dikmas Lantas cannot be separated from the purpose of the Kamseltibcar Lantas as a form of cooperation between the community and Polantas. Activities that become a means of Polantas in Dikmas Lantas are through counseling Police Goes to School. This study aims to find how the implementation and organizational resources of Dikmas Lantas by the Kamsel unit increase student traffic safety awareness at the Sragen Police. The study is qualitative research with data collection through interviews, observation, and documentation. Management theory, POAC, SWOT, principle of optimization, student concepts, and community education concepts were used as a literature review. The results of the study revealed that the implementation of Dikmas Lantas was good but not optimal because of inadequate organizational resources. The researcher suggests that the Unit of Sragen Police should focus on personnel development and adjustment of the Dikmas Lantas financial budget so that the implementation of Dikmas can run optimally.